Larvae of Australian Buprestidae (Coleoptera). Part 4. Genus Julodimorpha - Bílý, Svatopluk; Volkovitsh, Mark; Peterson, Magnus (Zootaxa, 2013)
The mature larva of the Australian buprestid genus Julodimorpha Gemminger and Harold, 1869 (J. saundersii Thomson, 1878) is fully described, illustrated and compared with the larvae of Julodinae, Polycestinae, Chrysochroinae, and Buprestinae. In situ observations confirm the soil inhabiting life-strategy of Julodimorpha larva. The comparative morphological study of the Julodimorpha larva proves its buprestine-chrysochroine affinities, while the superficial similarity of Julodimorpha and Julodinae adults, with their identical life-strategies, due to convergence.